Collectie Arnulf Rainer. - Dichter, Claudia; Fiselien, Saskia; Meijer, Saskia; Rainer, Arnulf; van Berkum, Ans (Zwolle : Museum De Stadshof, 1996)
Alcock, Pearl ; Bois-Vives, Anselme ; Corbaz, Aloïse ; Domenico, Leopold ; Duf, Gaston ; Gableck, Franz ; Ghizzardi, Pietro ; Gill, Madge ; Hauser, Johann ; Held, Margarethe ; Hueber, Wolfgang ; Jantosz, Jozef ; Kernbeis, Franz ; Korec, Johann ; L.L. ; Max ; Maly, Ida Franziska Sophia ; Nikifor ; Podesta, Giovanni ; Pous, Jean ; Raffler, Max ; Schöpke, Philipp ; Schröder-Sonnenstern, Friedrich ; Sekulic, Sava ; Soutter, Louis ; Theo ; Tschirtner, Oswald ; Uddin, Shafique ; Ulik, Ben ; Walla, August ; Wallis, Alfred ; Wilson, Scottie ; Wölfli, Adolf ; Zemankova, Anna
biografie
Collectie Arnulf Rainer, Museum De Stadshof, Zwolle, 21 september 1996 - 16 februari 1997
Nederlands & Duits
kunstcatalogus
Keywords: Rainer, Arnulf